Consumer Attitude Toward the Environmental Sustainability of Grain-Free Pet Foods - Conway, Danielle M. P.; Saker, Korinn E. (Frontiers in Veterinary Science, 2018)
For this study, we investigated consumer knowledge and attitude towards environmental sustainability, grain-free diets, and the influence of on-site environmental sustainability education on pet owner diet choices. A two-part questionnaire was designed, bracketing an educational brochure on environmental sustainability and grain-free diets. The study consisted of an informational brochure and two questionnaire sections, Q1and Q2. Preliminary information regarding current diets, diet choice(s), views of environmental sustainability, the definition of grain-free diets, and the likelihood of feeding grain-free diets were gathered via Q1. Participants then read a factual brochure regarding pet food trends and environmental sustainability. After reading the brochure, participants completed Q2. Pet ownership of the survey population indicated 12/78 cared exclusively for at least one cat, 48/78 cared exclusively for at least one dog, and 18 cared exclusively for at least one dog and one cat. The majority (70/78) of survey responders fed a dry commercial product, 25/78 fed a canned commercial product, and 1/78 fed a commercial raw product. Prior to reading the brochure, 44.9% of participants were able to partially identify a grain-free diet, 47.4% partially defined environmental sustainability, and 19.2% reported feeding a grain-free diet. After reading the brochure, 67.6% of participants were able to identify a more environmentally sustainable diet vs. 55.9% prior to reading the brochure. A paired T-test demonstrated that after reading the brochure, people were significantly less likely to feed a grain-free diet (p < 0.001). When participants already feeding a grain-free diet were isolated, they demonstrated a higher likelihood to feed a grain-free diet both before and after reading the pamphlet than the remaining population; however, the likelihood decreased from 8.4 2.7 to 7.8 2.7. The informational brochure was effective; participants were less likely to feed a grain-free diet after reading the brochure. Although participants considered environmental sustainability important, factors independent of environmental sustainability influenced the likelihood of diet change. Participants already feeding a grain-free diet also ranked environmental sustainability highly but were less likely to consider changing their pet’s diet. These preliminary findings identify a need for public education regarding pet food choices that can have environmental consequences.